Sidelobe level suppression for elliptical antenna arrays using modified SALP swarm algorithm - Kurt, Erhan; Basbug, Suad; Guney, Kerim (Journal of Electrical Engineering, 2022)
In this study, a modified version of salp swarm algorithm (MSSA) is used to synthesize elliptical antenna arrays (EAAs). The original salp swarm algorithm (SSA) is an optimization algorithm inspired by the behavior of salps in nature, which is used to solve engineering problems. The main purpose of the synthesis in this study is to obtain an EAA pattern with low maximum sidelobe levels (MSLs) for a fixed narrow first null beamwidth (FNBW). For different examples, the amplitude and angular position values of the antenna array elements are considered as optimization parameters. To show the effectiveness of the MSSA, eight examples of EAAs with 8, 12, and 20 elements are given. The results obtained with MSSA are compared with those of the antlion optimization, symbiotic organizations search, flower pollination algorithm, and accelerated particle swarm optimization from the literature. It is clear from the numerical results that MSSA outperforms the other algorithms in terms of the suppression of MSL.